Postoperative monitoring of local and free flaps with contrast-enhanced ultrasound (CEUS) - Analysis of 112 patients - Geis, S.; Prantl, L.; Dolderer, J.; Lamby, P.; Mueller, S.; Jung, E. M. (Ultraschall in der Medizin, 2013)
Purpose: Tissue defects are a common problem in trauma surgery and oncology. Flap transplantation is often the only therapy to cover such defects. Several monitoring systems are currently available but none has made it to the clinical routine. The aim of this study was to assess perfusion disturbances of local and free flaps using contrast-enhanced ultrasound (CEUS). Materials and Methods: 112 patients were examined during the first 72 hours after operation. CEUS was performed by one experienced examiner with a linear transducer (6-9MHz, LOGIQE9/GE) after a bolus injection of 2.4ml sulfohexa-fluoride microbubbles (SonoVue®, Bracco, Italy). Retrospective vascular perfusion was quantified by evaluating the stored DICOM cine loops using the perfusion software QONTRAST® (Bracco, Italy). Over a total penetration depth of 3cm, every centimeter was analyzed separately. 27 complications were observed. Complete flap loss was only seen in 4 cases, while 23 flaps had to undergo minor revision and survived. Results: Regarding the complete flap size, quantitative analysis showed significantly higher perfusion values in patients without complications compared to patients with complications: PEAK 16.5 vs. 10.0 (p=0.001), TTP 32.6 vs. 22.2 (p=0.001), RBV: 738.8 vs. 246.2 (p<0.001), RBF 17.5 vs. 10.1 (p<0.001) and MTT 43.1 vs. 29.5 (p=0.001). Analysis of the correlation of the different flap types, age, sex and etiology of the tissue defect to the complication rate showed no statistical correlation. Conclusion: CEUS was capable of detecting vascular disturbances after flap transplantation. TTP, RBV and MTT seem to be the most accurately parameters and are not susceptible to malfunction during measurement. © 2013 Georg Thieme Verlag KG Stuttgart New York.
CRIS-Team Scopus Importer:2024-12-11
Keywords: contrast-enhanced ultrasound (CEUS); perfusion monitoring; skin; soft tissues; ultrasound